Identification of Protein Kinase Inhibitory Activities Fromstreptomyces Strain H7372 for Potential Use As Anti-Canceragent - Hassan, Masriana (2007)
Aberrations in the phospbatidylinositol3-kinase (PI3K)IAkt pathway have been found in a wide spectrum of human cancers. Activation of Akt and inactivation of the downstream substrates such as GSK-3P, BAD and Forkhead family (FKHR) proteins are relevant to promote cell survival, proliferation and growth. Another related pathway linked with PI3K/Akt is the Ras/Raf/MEK/ERK, which is known to promote cancer as a result of ras-transformation. The discovery of new drugs targeted at specific molecules of these pathways is a 'hot' field in cancer research. Blocking the constitutively active PI3WAkt pathway provides a new strategy for cancer therapy. Thus, inhibitors of this signaling pathway would be potential anti-cancer agents. The Streptomyces strain H7372 isolated h m mangrove soils in Sabah was found to inhibit the Ras/Raf-1 protein interaction in the yeast two-hybrid screening system. The present study was undertaken to determine the cytotoxic effect of H7372 hctionated extract on a breast cancer cell line, MCF-7 and a non-tumorigenic epithelial cell line, MCF-1OA and quantitatively measure kinase inhibition, apoptosis induction and cell cycle disruption. The crude iii extracts of H7372 were fractionated into eight Eractions using reverse phase HPLC. Fraction 5 was found to be the most cytotoxic in an M'IT assay. The crude extract and fraction 5 of H7372 were found to exert growth inhibition of MCF-7 at ICS0 of 15&nl and 1.4 pglml, respectively. Western blot analyses showed that activated PI3K and Akt (Thr308) but not Akt (Ser473) by stimulation of IGF-I were inhibited by the crude extract and fraction 5 after 72 hours. Interestingly, phosphorylation of Raf-1 (Ser259) and ERKl were also inhibited by fraction 5, indicated that there is a cross-talk between PI3WAkl and MAPK pathways. By using the flow cytometry technique, we found that fraction 5 inhibited the proliferation of MCF-7 cell line by causing them to arrest in the GI phase of the cell cycle. The induction of growth arrest by fraction 5 was associated with accumulation of cells in GI and decreasing cells in S and G2/M phases. The results were supported by inihibition of cyclin Dl in MCF-7 cells. The apoptosis study showed that fraction 5 but not crude extract was increased the percentage of cells in early apoptotic stage at all concentrations. Furthermore, treatment of MCF-7 cells with fraction 5 resulted in reduction in phosphorylation of GSK-3$ (Ser9), phospho-BAD (Serll2) and phospho-FKHR (Ser256). These results could contribute the apoptosis in MCF-7 cell line. Thus, we discovered that k t i o n 5 of H7372, a naturally occurring microbe, contains an inhibitor of cell proliferation, cell cycle progression and is able to induce apoptosis via the PI3WAkl and MAPK pathways.